2008
DOI: 10.1007/s00572-008-0166-5
|View full text |Cite
|
Sign up to set email alerts
|

Belowground ectomycorrhizal communities in three Norway spruce stands with different degrees of decline in the Czech Republic

Abstract: We investigated the ectomycorrhizal communities on the roots of adult trees and seedlings associated with three Norway spruce stands in the Czech Republic using morphological and molecular tools. The stands had different degrees of forest decline due to air pollution. The aims of the study were to obtain information about the belowground ectomycorrhizal community in a heavily damaged spruce forest and to assess whether missing ectomycorrhizal fungal partners could be one of the reasons for the observed lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…In particular, detailed molecular characterization of the fungi colonizing roots is required in order to identify those ECM species that are sensitive to canopy decline of E. gomphocephala. Previous studies in other forest systems have demonstrated that defoliation might affect ECM fungi through carbon allocation to roots (Markkola et al 2004;Peter et al 2008). The situation is complex as ECM fungi may contribute to forest resilience, recovery, and vigor (Amaranthus 1998) as well as plant biodiversity and productivity in natural ecosystems (van der Heijden et al 1998;van der Heijden and van Straalen 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, detailed molecular characterization of the fungi colonizing roots is required in order to identify those ECM species that are sensitive to canopy decline of E. gomphocephala. Previous studies in other forest systems have demonstrated that defoliation might affect ECM fungi through carbon allocation to roots (Markkola et al 2004;Peter et al 2008). The situation is complex as ECM fungi may contribute to forest resilience, recovery, and vigor (Amaranthus 1998) as well as plant biodiversity and productivity in natural ecosystems (van der Heijden et al 1998;van der Heijden and van Straalen 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the canopy condition of E. gomphocephala in the field may impact on spore production by mycorrhizal fungi. It is generally assumed that ECM associations obtain more energy from host plants than AM associations (Smith and Read 2008) and the amount of carbon allocated below ground can influence populations of mycorrhizal fungi (Peter et al 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction in species was not limited to estimates based on fruiting bodies but was also confirmed using DNA identification methods on EM roottips. In a field investigation in the Czech Republic, Peter et al (2008) obtained information about the EMF community in a heavily-damaged spruce forest and assessed whether missing EMF partners could contribute to the observed lack of regeneration. The EM species richness on the roots of adult trees was significantly lower in the heavily-damaged site than in the other two sites.…”
Section: Studies With Other Abiotic Factorsmentioning
confidence: 99%
“…This is because although fruit-bodies are necessarily associated with ectomycorrhizae, a fungus-forming ectomycorrhiza may not always form sporocarps, which are affected by biotic and abiotic factors in natural ecosystems (Horton and Bruns 2001). Advances in molecular techniques have allowed consistent identification of ECM fungi and have facilitated research in natural ecosystems (Peter et al 2008). Molecular studies on ECM communities have been widely carried out in temperate and boreal ecosystems (Ishida et al 2009;Wang and Guo 2010), as well as in tropical regions (Morris et al 2008;Peay et al 2010).…”
Section: Introductionmentioning
confidence: 99%